Application of FT-IR spectroscopy to the specific migration study of an organotin heat stabilizer from rigid poly(vinyl chloride) into food simulants - Zeddam, Ch.; Belhaneche-Bensemra, N. (Polimery, 2011)
The specific migration of an organotin heat stabilizer (Irgastab 17 M0K) from rigid poly(vinyl chloride) (PVC) into food simulants is investigated. For that purpose, two fatty simulants were used: hexane and ethanol. The test conditions were 15 days at 4 °C and 40 °C and 3 hours at 70 °C. The rate of the mass variation of the films was followed as a function of time. FT-IR spectroscopy was used to investigate the migration phenomena and to estimate the diffusion coefficients by using mathematical models. The influence of various parameters such as temperature, time of contact and the nature of food simulant was considered.